The city of Askar Makram and its general conditions, from the Arab conquest to the fall of the Buoyan emirate: (13-451 AH / 634 - 1059 AD) - Al-Fayyad, Ali Najm Abdullah (Al-Adab Journal, 2020)
The Arabs have paid attention to the Islamic conquest, in the era of the two caliphs Abu Bakr Al-Siddiq and Omar Bin Al-Khattab (may God be pleased with them) (11-23 AH / 632-643 AD). And after that, the conquest operations came from here. Until the fall of the Buoyan emirate (13-451 AH / 634 - 1059 AD), "Askar Makram is a city with many blacks and a picnic with a blessing, including sugar, which works the horizons of red, white and Qand, so agricultural production is the backbone that supplies the population with most of their needs.